Emotional Intelligence and Team Creativity: An empirical investigation of Small and Medium sized enterprises in Saudi Arabia - Ba Saiwar, Wedyan Salmen; Badawi, Nada Saleh (Journal of Economic, Administrative and Legal Sciences, 2022)
This study aims to examines the link between Emotional Intelligence and team creativity in small and medium enterprises in Saudi Arabia. It attempts to fill the gap in the literature by addressing the question: Is there a significant relationship between emotional intelligence and team creativity in SMEs?. The data were collected through online questionnaires from 476 employees, managers, and owners of small and medium enterprises in Saudi Arabia. The results show a significant positive relationship between emotional intelligence and team creativity in SMEs. Results provide practical implications for managers in small and medium enterprises which aid them to design effective strategies that can boost creativity at the team level.